EFFICIENT WAYS OF COMBATING AGAINST PEAR PSYLLA (Proceedings of the YSU B: Chemical and Biological Sciences, 2017)
During 2013–2015 the foliage population of trees from different sides with ordinary pear psylla was studied. At the same time based on estimation the population of various parts of trees with this phytophagous has been identified. It was found out that in considerably shadow, poorly illuminated parts (north and west) of pear habitus, the population of plants with psylla has been lower than in eastern and northern parts. Therefore, in the process of undertaking chemical control is important to spray intensively the lower level of pear leaves with working solution.
Keywords: pear, ordinary psylla, harmfulness, tree habitus, population